2008
DOI: 10.2754/avb200877040547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Live Yeast Culture (Saccharomyces cerevisiae) on Milk Production and Composition, and Blood Biochemistry of Grazing Dairy Ewes during the Milking Period

Abstract: A feeding trial was conducted to evaluate the influence of live yeast culture (Saccharomyces cerevisiae) on milk production, composition, and blood biochemistry of dairy ewes during the machine milking period.The control group (CD) was fed a concentrate mixture and hay and grazed twice daily, while the second (YS3) and third (YS6) groups were fed the same diet supplemented with 3 or 6 g of live yeast culture (Yea Sacc 1026 ), respectively. The treated groups had significantly higher values (p < 0.05) for fat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
7
14
1
1
Order By: Relevance
“…In this study the inclusion of yeast culture had no effect on milk composition, which is in agreement with Mašek et al (2008a) who found no influence of added 3 or 6 g/head/day of live yeast in the diet Istrian sheep × East Freisian dairy ewes. On the contrary, Mašek et al (2008b) found increases in the milk fat content of Croatian crossbred dairy ewes supplemented to 1 g/head/day of live yeast cells.…”
Section: Milk Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study the inclusion of yeast culture had no effect on milk composition, which is in agreement with Mašek et al (2008a) who found no influence of added 3 or 6 g/head/day of live yeast in the diet Istrian sheep × East Freisian dairy ewes. On the contrary, Mašek et al (2008b) found increases in the milk fat content of Croatian crossbred dairy ewes supplemented to 1 g/head/day of live yeast cells.…”
Section: Milk Compositionsupporting
confidence: 92%
“…In sheep, results of recent studies are also variable. Mašek et al (2008a) found no effect of the addition of live yeast on milk quality, while in another study increased the fat content (Mašek et al 2008b).…”
Section: Introductionmentioning
confidence: 97%
“…Milk urea nitrogen was significantly lower in the LY group (P 00.001). The decrease in urea level in milk and blood (Table 5) was probably related to a higher microbial activity and higher incorporation of NH 3 into microbial protein (Erasmus et al 1992;Masˇek et al 2008;Heidari Khormizi et al 2010). Increasing NDF apparent digestibility approved this hypothesis (Table 3).…”
Section: Resultsmentioning
confidence: 78%
“…Supplementing dairy cow diets with Direct Fed Microbial (DFM) is one way to reduce these effects (Bruno et al 2009). The use of DFM as a feed additive for manipulating rumen fermentation, in order to reduce energy and nutrient losses from commercial ruminant production, has been extensively investigated since the 1950s (Guedes et al 2008;Masˇek et al 2008). Saccharomyces cerevisiae is the most common DFM recently supplemented to the diet of lactating dairy cows (Thrune et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Szucs, Suli, Halasz, Arany, and Bodor (), who gave live yeast (strain CNCM I‐4407; 5 g/cow/day) to transition dairy cows under field conditions, found reduced serum levels of BHBA and NEFA. On the contrary, Baiomy () and Mašek et al () found increased levels of BHBA and NEFA in live yeast culture‐supplemented ewes. Nikkah, Bonadaki, and Zali () did not demonstrate significant effects on the metabolic profile of lactating cows after S. cerevisiae feed supplementation; they did not find any changes in the levels of glucose.…”
Section: Discussionmentioning
confidence: 92%